Penggunaan Pupuk Organik sebagai Solusi untuk Mengatasi Kekurangan Pupuk Kimia pada Budidaya Padi di Desa Mentayan Kecamatan Bantan Kabupaten Bengkalis Provinsi Riau - Bahri, Saipul; Dewi, Ilma Satriana; Mardaleni Mardaleni; Ujang Paman Ismail (Lembaga Pengembangan Kinerja Dosen, 2025)
Rice plants as a source of food production are really needed by the community. Mentayan Village develops rice fields that use rainwater as a source of irrigation. There is a farmer group in the area known as the Bina Maju farmer group. This farmer group has problems or obstacles in cultivation such as lack of use of fertilizer, rare and high prices of chemical fertilizers and lack of subsidies and fertilizer assistance from the government which can affect the amount of rice produced. This service is carried out with the aim of providing solutions to problems in the Bina Maju farmer group. The solution to the problems faced by this farmer group can be solved by using organic fertilizer. The implementation method for socialization is to explain in detail and clearly about organic fertilizer using the lecture and discussion method between the service team and a demonstration of making organic fertilizer that can be applied to rice plants. Based on the service activities, the results obtained were that the activity participants had understood the material about making organic fertilizer and could then practice it and produce organic fertilizer independently to overcome the shortage of chemical fertilizers in rice plants.